Use of data mining to identify trends between variables to improve implementation of an immersive environment (2017)
Globally, the implementation of immersive environments for leaming activities have been in constant growth whch indcates that their development must improve daily. For this reason, this study identifies trends (co-occurrences) and relatiomhps between variables associated with an immersive environment to improve its implementation. Results were found which show that a good design of information guides, organization of menus and useful instructiom generates that the users enjoy using the immersive environment for leaming and foments recommendations of use to other users.